2011
DOI: 10.1007/s00702-011-0714-6
|View full text |Cite
|
Sign up to set email alerts
|

ApoE gene polymorphism and vascular dementia in Chinese population: a meta-analysis

Abstract: Vascular dementia is the second common cause of dementia, only second to Alzheimer's disease in later life. The Apolipoprotein E (ApoE) gene polymorphism as a risk factor in vascular dementia has been suggested, but direct evidence from genetic association studies remains inconclusive even in Chinese population. Therefore, we performed this meta-analysis in order to evaluate the relationship between ApoE gene polymorphism and susceptibility to vascular dementia in Chinese population by pooling data from all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…5,9,[16][17][18][19]22,25 The data on subtypes of dementia and cerebrovascular disease show that the ε42 genotype is more important than the ε43 genotype for vascular components of dementia, as well as for cerebrovascular disease, than previously reported. [11][12][13][14][15][16][17][18][19] This is biologically plausible, given that the ε42 genotype is a combination of 2 hyperlipidemic alleles: ε2 has low receptor affinity for the LDL receptor, resulting in susceptibility to type III hyperlipoproteinemia with increased levels of triglycerides and remnant particles, 7,29 whereas ε4 is associated with increased plasma levels of LDL cholesterol and triglycerides. 30 The decreased receptor affinity for apoE2 leads to a decreased apoE-mediated uptake and an upregulation of the LDL receptor, probably explaining the associated low LDL cholesterol and high triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,[16][17][18][19]22,25 The data on subtypes of dementia and cerebrovascular disease show that the ε42 genotype is more important than the ε43 genotype for vascular components of dementia, as well as for cerebrovascular disease, than previously reported. [11][12][13][14][15][16][17][18][19] This is biologically plausible, given that the ε42 genotype is a combination of 2 hyperlipidemic alleles: ε2 has low receptor affinity for the LDL receptor, resulting in susceptibility to type III hyperlipoproteinemia with increased levels of triglycerides and remnant particles, 7,29 whereas ε4 is associated with increased plasma levels of LDL cholesterol and triglycerides. 30 The decreased receptor affinity for apoE2 leads to a decreased apoE-mediated uptake and an upregulation of the LDL receptor, probably explaining the associated low LDL cholesterol and high triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the association between APOE-ε4 and VaD are equivocal. A meta-analysis of Chinese Han showed a pooled Odds Ratio (OR) of 2.07 (95% CI: 1.69, 2.53) for VaD 33 . However, another study of older Japanese conducted in Hisayama, Japan found no association between ε4 and VaD (RR=1.08, p =0.86) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have further suggested that the APOE e4 allele is also a genetic risk factor (albeit a weaker one) for other forms of dementia, such as vascular dementia (Liu et al, 2012;Rohn, 2014) and dementias with synucleinopathy Tsuang et al, 2013), even if it is not settled to which degree such associations exist since patients with these disorders have concomitant cerebral amyloid b pathology (Lim et al, 1999;Lopez et al, 2002;Neuropathology Group of the Medical Research Council Cognitive Function and Aging Study, 2001). However, not all people carrying the APOE e4 allele develop Alzheimer's disease or dementia, whereas some people without the APOE e4 allele do (Blennow, Hampel, Weiner, & Zetterberg, 2010;Blennow et al, 2006;Prince, Zetterberg, Andreasen, Marcusson, & Blennow, 2004).…”
Section: The Apoe E4 Allele and Dementiamentioning
confidence: 99%